Assessing the toxicity and risk of salt-impacted winter road runoff to the early life stages of freshwater mussels in the Canadian province of Ontario. (November 2017) - Prosser, R.S.; Rochfort, Q.; McInnis, R.; Exall, K.; Gillis, P.L.
Abstract: In temperate urbanized areas where road salting is used for winter road maintenance, the level of chloride in surface waters has been increasing. While a number of studies have shown that the early-life stages of freshwater mussels are particularly sensitive to salt; few studies have examined the toxicity of salt-impacted winter road runoff to the early-life stages of freshwater mussels to confirm that chloride is the driver of toxicity in this mixture. This study examines the acute toxicity of field-collected winter road runoff to the glochidia of wavy-rayed lampmussels ( Lampsilis fasciola ) (48 h exposure) and newly released juvenile fatmucket mussels ( Lampsilis siliquoidea ) (<1 week old; 96 h exposure) under different water hardness. The chronic toxicity (28 d) to older juvenile L. siliquoidea (7–12 months old) was also investigated. The 48-h EC50 and 96-h LC50 for L. fasciola glochidia and L. siliquoidea juveniles exposed to different dilutions of road run-off created with moderately hard synthetic water (∼80 mg CaCO3 /L) were 1177 (95% confidence interval (CI): 1011–1344 mg Cl − /L) and 2276 mg Cl − /L (95% CI: 1698–2854 mg Cl − /L), respectively. These effect concentrations correspond with the toxicity of chloride reported in other studies, indicating that chloride is likely the driver of toxicity in salt-impacted road-runoff, with other contaminants (e.g., metals, polycyclic aromatic hydrocarbons) playing a de minimis role. Toxicity data from the current study and literature and concentrations of chloride in the surface waters of Ontario were used to conduct a probabilistic risk assessment of chloride to early-life stage freshwater mussels. The assessment indicated that chronic exposure to elevated chloride levels could pose a risk to freshwater mussels; further investigation is warranted to ensure that the most sensitive organisms are protected. Graphical abstract: Highlights: Salt-laden winter road runoff was toxic to early life stage freshwater mussels. Chloride is main driver of toxicity in winter road runoff. A probabilistic risk assessment of chloride to mussels in Ontario was performed. Assessment revealed chronic exposure to chloride poses a risk to freshwater mussels. Further research on chronic salt exposure is needed to understand this risk.